2015
DOI: 10.1097/md.0000000000002279
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated Contrast Medium Exposure During Computed Tomography Increase the Risk of Subsequent Development of Thyroid Disorders in Patients Without Known Thyroid Disease

Abstract: To investigate the association between iodinated contrast medium (ICM) exposure during computed tomography (CT) and the subsequent development of thyroid disorders in patients without known thyroid disease in Taiwan, an iodine-sufficient area.We conducted a population-based cohort study by using data from 1996 to 2012 in the Taiwan National Health Insurance Research Database. A total of 33,426 patients who underwent ICM-enhanced CT were included as the study cohort. To avoid selection bias, we used propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…An average 1,5 − 2 ml dosage of ICM with a 35µg/ml concentration is used in the procedure, providing 70µg of free iodide, which is much lower than CT or angiography ranges [11,12]. Some research indicates that repeated ICM exposure and large ICM volumes are more likely to elevate the risk of thyroid disorders [13,14]. Contrary to these studies, we found no correlation between contrast volume and thyroid hormone dysregulation.…”
Section: Discussioncontrasting
confidence: 87%
“…An average 1,5 − 2 ml dosage of ICM with a 35µg/ml concentration is used in the procedure, providing 70µg of free iodide, which is much lower than CT or angiography ranges [11,12]. Some research indicates that repeated ICM exposure and large ICM volumes are more likely to elevate the risk of thyroid disorders [13,14]. Contrary to these studies, we found no correlation between contrast volume and thyroid hormone dysregulation.…”
Section: Discussioncontrasting
confidence: 87%
“…Third, senior physicians should audit the orders of CT scans by junior physicians in the ED. 17 27 28 …”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher risk of ICM-induced TD (based on International Classification of Diseases, Ninth Revision, Clinical Modification codes) was demonstrated in Taiwan among 1 million patients in the general population over a single year time period; the adjusted hazard ratio (HR) of Hyper and Hypo compared with controls was 1.22 (95% CI, 1.04–1.44) and 2.00 (95% CI, 1.65–2.44), respectively [14]. Moreover repeated ICM exposure (>1 time of ICM per year) increased significantly the risk of thyroid disorders (HR = 3.04; 95% CI, 2.47–3.73) [15]. A subsequent study using the Taiwan’s National Health Insurance Research Database found that patients with euthyroid nodular goiter had almost 5-fold higher risk of ICM-induced TD than patients without thyroid nodule(s), including Hyper (HR 5.77, CI 2.64–12.62) and Hypo (HR 4.95, CI 2.15–11.40) [16].…”
Section: Introductionmentioning
confidence: 99%